The Influence of Profit Sharing Rates on Mudharabah Deposit Savings of the Islamic People's Economic Bank, HIK Parahyangan, Indramayu Branch - Afinda Syaebani (Konsultan Jurnal Ilmiah Indonesia, 2025)
This research aims to analyze the influence of the level of profit sharing on customers' decisions in choosing mudharabah deposit products at BPRS Hik Parahyangan. Mudharabah deposits are a sharia banking product that offers sharing of business results between the bank and customers based on an agreed ratio. The findings of this research indicate that the level of profit sharing has a significant influence on customers' decisions to invest in mudharabah deposit products. The higher the level of profit sharing offered, the greater the customer's interest in placing their funds. However, other factors such as bank reputation, economic conditions and risk management also influence customer decisions. BPRS Hik Parahyangan needs to maintain a balance between offering competitive profit sharing rates and ensuring the continuity of bank operations through careful risk management. Apart from that, a good bank reputation and transparent fund management are important factors in building customer trust. This research provides recommendations for BPRS Hik Parahyangan to pay attention to these factors in its mudharabah deposit management strategy in order to increase customer satisfaction and loyalty.